How can family businesses survive disruptive industry changes? Insights from the traditional mail order industry - Julia K. de Groote; Werner Conrad; Andreas Hack (Review of Managerial Science, 2020)
The present study investigates how family firms respond to disruptive industry changes. We aim to investigate which factors prevent or support family firms' adoption of disruptive innovations in their industry and which mechanisms lead to more or less successful coping with disruptive change. Our analysis is based on 24 qualitative interviews with top executives and on secondary data from an industry in which disruptive innovations dramatically changed the way business was generated. The industry in question is the mail order industry, which, in its early days, disrupted the retail business. When the Internet and, with it, ecommerce started to disrupt the industry in the late 1990s, the industry was characterized by a high proportion of family firms and a low level of innovativeness. While incumbent firms had been very successful for decades, most of them were confronted with serious turbulence when new entrants started changing the face of the industry. Our findings show that different factors impact reactions to disruptive industry change in two different phases, namely, opportunity recognition and opportunity implementation. While some of the influencing factors are determined by industry factors, family influence may function for better or worse for incumbent firms. Specifically, we find that in firms with a family disruptor, a family member in a powerful position who drives the adoption of the new technology, hindrances can be overcome and firms tend to show more successful strategies when reacting to the disruptive industry change.
Keywords: 650; Disruptive innovation; Family firms; Ecommerce; Opportunity recognition; Opportunity implementation; -02